Avoidable causes of cancellation in elective orthopaedic surgery. - Wildner, M; Bulstrode, C; Spivey, J; Carr, A; Nugent, I (1991)
As part of an audit of clinical practice in an orthopaedic unit for elective surgery, a study was made of the causes of cancellation of operations. Despite careful liaison with general practitioners, and a booked admission policy, over 6% of patients were cancelled as unsuitable. The results of this study suggest that the number of cancellations on medical grounds would be reduced by closer liaison with general practitioners, and the establishment of preadmission clinics. Ensuring that only consultants book patients for surgery would also reduce the number of cancellations due to incorrect indications for surgery.